2023
DOI: 10.3390/molecules28031472
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Annealing Effect on Surface-Enhanced Raman Scattering of Gold Films Deposited on Liquid Substrates

Abstract: We prepare metal films with various thicknesses on liquid substrates by thermal evaporation and investigate the annealing effect on these films. Gold films deposited on a silicone oil surface consist of a large number of branched aggregates, which contains plenty of gold nanoparticles. This characteristic morphology is mainly attributed to the isotropic and free-sustained liquid substrate. Thermal annealing results in the reintegration of nanoparticles; thus, the surface morphology and microstructure of gold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…The STO was then removed from the sample surface and a sequential washing by acetone and methanol was performed on the STO to remove the oil on the surface. This unique NP separation and washing process have been frequently adapted in previous work because NPs are highly stable on the crystal surface for days [35][36][37][38]. After washing, the NP/STO system was pumped in the vacuum chamber for 0.5 h. The NP/STO sample was then kept in a container which was initially pumped and transferred to scanning electron microscopic (ZEISS SUPRA 55 SAPPHIRE, Carl Zeiss, Shanghai, China) study.…”
Section: Methodsmentioning
confidence: 99%
“…The STO was then removed from the sample surface and a sequential washing by acetone and methanol was performed on the STO to remove the oil on the surface. This unique NP separation and washing process have been frequently adapted in previous work because NPs are highly stable on the crystal surface for days [35][36][37][38]. After washing, the NP/STO system was pumped in the vacuum chamber for 0.5 h. The NP/STO sample was then kept in a container which was initially pumped and transferred to scanning electron microscopic (ZEISS SUPRA 55 SAPPHIRE, Carl Zeiss, Shanghai, China) study.…”
Section: Methodsmentioning
confidence: 99%
“…Although the mineral sample was acquired as azurite, the peaks at 121, 194, and 458 cm À 1 found in the Raman-SERS analysis are associated with a quartz mineral as it can be seen in Figure a) where the mineral sample is compared with a known fragment of quartz that has the correspondent Raman bands of quart (14,1945 and 1945 cm À 1 ). SEM micrographs and EDS analysis revealed that the blue mineral is mainly composed of a heterogeneous mixture of two phases (Figure b), with copper and silicon being the two main constituents of these phases (encircled areas in Figure b).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…On the other hand, although the use of metallic nanoparticles in suspension is an alternative to generate the SERS effect, this effect can also be obtained by immobilizing nanoparticles on solid substrates. [10,14] According to this aspect, in recent years it has sought to develop removable devices that meet the objective of presenting the SERS effect, and that can be used to analyze different types of analytes without interfering with the integrity of the sample. [15,16] Immobilization of metal nanoparticles on flexible substrates such as gelatin, [17] or methylcellulose pastes, [18] the use of organic polymer-based substrates such as poly(vinyl pyridine) to deposit silver nanoparticles, [19] or poly(vinyl pyrrolidone) to deposit gold nanoparticles, [20] and more recently the use of poly(dimethyl siloxane) (PDMS) to immobilize AgNPs [21,22] are some promising alternatives developed that could achieve such a goal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations